Intergenerational metabolic toxicity of perfluorooctanesulfonic acid exposure in adult offspring rats: a multi-omics approach - Yu, Guoqi; Luo, Tingyu; Huo, Xiaona; Meng, Xi; Feng, Liping; Sun, Yan; Liu, Yongjie; Zhang, Jun (Frontiers in Endocrinology, 2025)
IntroductionPerfluorooctane sulfonate (PFOS), known as a critical endocrine disruptor, was linked to potential intergenerational effect in population studies. Yet, the toxic metabolic mechanisms remain unclear, particularly at relatively low PFOS concentration.MethodsThis study investigated the metabolic impacts of early-life (pregnancy and lactation) PFOS exposure on adult Sprague-Dawley (SD) offspring rats using an integrated transcriptomics and metabolomics approach. Metabolic phenotypes, including glucose tolerance, lipids, and metabolic biomarkers were measured.ResultsEarly-life exposure to 0.03 mg/kg PFOS was found to be associated with elevated fasting and 15-minute blood glucose, serum insulin, and adiponectin levels and a decrease of leptin level in dose of 0.3 mg/kg was observed. Differentially expressed genes induced by PFOS exposure were enriched in NOD-like receptor signaling, parathyroid hormone synthesis, secretion and action, unsaturated fatty acid biosynthesis, insulin signaling, retinol metabolism, fatty acid metabolism, glucagon signaling, type II diabetes, and PPAR signaling. Differentially expressed metabolites were linked to citric acid cycle, glycerophospholipid metabolism, and fatty acid biosynthesis. Coenrichment analysis revealed feature changes in several pathways, including glycerophospholipid metabolism, sphingolipid metabolism, and primary bile acid synthesis (0.03 mg/kg), and retinol metabolism, linoleic acid metabolism, DGlutamine and D-Glutamine biosynthesis, and fatty acid elongation (0.3 mg/kg). ConclusionEarly-life exposure to PFOS might lead to metabolic perturbations in adult offspring, which might be triggered by changes in pathways, i.g. glycerophospholipid metabolism, retinol metabolism, linoleic acid metabolism, and fatty acid elongation. Further validation of these pathways is required.